Aspects regarding the uncertainty of spatial statistical models of climate parameters - CRISTIAN VALERIU, Patriche (Idoejaras, 2011)
Any transformation of a discrete variable into a continuous one is subject to uncertainty. Consequently, the identification and assessment of errors is essential for avoiding misinterpretations of models describing the spatial distribution of climatic parameters. Our study attempts to identify the main sources of errors affecting the statistical spatial models of climatic parameters and to assess their impact on the accuracy of these models. In particular, we focus on georeference errors, the representativeness of the stations network and the related extrapolation problem, the outliers problem, error propagation from simple to complex variables, the problems aroused by heterogeneous regions.